Nutritional Properties Evaluation of Blowfly Larvae from Fish and Chicken Wastes for Asian Sea Bass Feed Formulation Application: Nutritional Properties Evaluation of Blowfly Larvae - Anuar, Nurazira; Omar, Nur Faizah Moidu; Zakaria, Zainoha; Abdul Keyon, Aemi Syazwani; Muda, Nor Wajihan; Abd. Manaf, Mohammed Suhaimee; Mahat, Naji Arafat (Journal of Tropical Life Science, 2023)
This present research characterized the proximate nutrient, fatty acids and amino acids compositions of the wild third instar blowfly larvae collected from fish and chicken wastes as well as its mixture, in view of aquaculture feeding for Asian sea bass (Lates calcarifer). Analyses of crude protein, crude lipids, crude fiber, ash, carbohydrates, amino as well as fatty acids were performed. Results revealed that the larvae that fed on the mixed substrates (chicken and fish, 50:50 ratio) had significantly the highest nutritional values (51.47 ± 0.32% of crude protein, 29.4 ± 1.47% of crude fat, 4.81 ± 0.83% of crude fiber, 4.85 ± 0.01% of ash and 12.71 ± 1.67% of carbohydrate) for formulating feeds for Asian sea bass when compared with that of chicken and fish wastes alone (P < 0.05). Similarly, significantly higher percentages of fatty acids (DHA and EPA) and amino acids (Arg, Lys, Met, Trp, His, Val, Ile, Leu and Phe) were observed in the larvae from mixed-substrates when compared with that of the remaining two substrates (P < 0.05). The findings supported the utilization of blowfly larvae harvested on mixed substrate as a possible candidate of nutrients for Asian sea bass feed formulations